A critical appraisal of Freud’s ideas on man and personality - Abdul Razak, Mohd Abbas; Ismail, Nik Ahmad Hisham (International Islamic University Malaysia, 2013)
Since ancient times, scholars in the West have shown great enthusiasm towards understanding the subject on man and personality. Driven by this zeal, there appeared a multitude of theories discussing man and his nature. Various concepts on man showcased by the scholars, quite often, complemented one another and, at times, their ideas contradicted and discredited one another. Sigmund Freud (1856-1939) the founding father of psychoanalysis presented to the world a concept on man and his personality which turned out to be a controversial one. His idea of man seems to have shaped the western culture and human psyche in general. What appears from the impact of Freud’s concept of man and personality is that it has denigrated man. This paper represents an appraisal of his idea of man and personality from human angle.